Predictor of smoking cessation among school-going adolescents in Indonesia: a secondary analysis based on the transtheoretical model of behavioral change - Dadras, Omid (Frontiers in Psychiatry, 2024)
Introduction This study elucidates the complex journey of adolescents toward smoking cessation, investigating the association of relevant demographic factors, advertising, promotion, anti-cigarette messages, and individual knowledge and attitudes with being in different smoking cessation stages. Methods Utilizing data from the 2019 Indonesia Global Youth Tobacco Survey, this secondary analysis included adolescents who reported ever smoking. The Transtheoretical Model (TTM) guided the categorization of the outcome variable into three smoking cessation stages based on the responses to two questions related to the intention and timing of the smoking cessation. This included contemplation, action, and maintenance stages. Multinomial logistic regression analyzed the associations between each independent variable and being in each stage of smoking cessation. The study comprised 3596 Indonesian adolescents from grades 7-12, of which 2484 responded to two questions related to intention and timing of smoking cessation and were included in regression analysis. Results Findings indicate that males and those aged ≥16 were predominantly in contemplation phase. Early smoking initiation, usage of other tobacco products, and exposure to various forms of smoke increased the likelihood of being in contemplation and action phases. Parental smoking, school smoking exposure, and second-hand smoke were significant contemplation phase predictors. Exposure to tobacco advertising was linked to an increased likelihood of being in contemplation and action phases, whereas anti-cigarette messages showed no significant impact. Awareness of cigarette and second-hand smoke harms reduced the odds of being in the contemplation phase, while enjoying smoking and willingness to accept cigarettes from friends increased the odds of being in contemplation and action phases rather than in maintenance phase. Conclusion Addressing age, gender, cultural influences, environmental factors, and attitudes towards smoking through tailored interventions is vital for aiding smoking cessation in Indonesian adolescents. Strengthened tobacco control in schools and public places is recommended to bolster these efforts. Longitudinal studies are required to explore the evolving patterns of smoking cessation behaviors over time, enhancing our understanding of the factors influencing sustained cessation.